Solving Partial Differential Equations Using Fourier Series - Munira Hadya; Sana Maetouq; Mouna Salamah (AlQalam Journal of Medical and Applied Sciences, 2024)
This research paper aims to study the methods of solving partial differential equations using Fourier series. Partial differential equations are a powerful and practical tool in mathematics and physics to describe many phenomena and processes that involve continuous change at the level of equations and functions. The basic concepts related to the Fourier series and how to represent functions using it in the field of mathematics will be reviewed. Application examples of partial differential equations, such as waves, heat and diffusion, and how to use the Fourier series to solve them will also be presented. The steps of solving the partial differential equation using the Fourier series will be explained. The importance of Fourier series in the theory of partial differential equations is that periodic functions f(x) defined on (-∞,∞) or functions defined on a finite interval can be represented by an infinite interval of sines and cosines. In this research, the solution of the partial differential equation using the Fourier series was studied with the solution of an example. تستهدف هذه الورقة البحثية دراسة طرق حل المعادلات التفاضلية الجزئية باستخدام متسلسلة فورييه. تعد المعادلات التفاضلية الجزئية أداة قوية وعملية في علم الرياضيات والفيزياء لوصف العديد من الظواهر والعمليات التي تتضمن تغيرًا مستمرًا على مستوى المعادلات والدوال.ستتم مراجعة المفاهيم الأساسية المتعلقة بالمتسلسلة الفورييه وكيفية تمثيل الدوال باستخدامها في مجال الرياضيات. سيتم أيضًا تقديم أمثلة تطبيقية للمعادلات التفاضلية الجزئية، مثل الموجة والحرارة والانتشار، وكيفية استخدام متسلسلة فورييه لحلها.سيتم توضيح خطوات حل المعادلة التفاضلية الجزئية باستخدام متسلسلة فورييه. أن أهمية سلاسل فورية في نظرية المعادلات التفاضلية الجزئية هي إنالدوال الدورية f(x)المعرفة علي∞,∞- )) أو الدوال المعرفة علي فترة منتهيةيمكن تمثيلها فترة لانهائية من الجيوب وجيوب التمام و في هذا البحث تمت دراسة حل المعادلة التفاضلية الجزئية باستخدام متسلسلة فورييه مع حل مثال